Developing “Smartness” in Emerging Environments and Applications with Focus on the Internet of Things (IoT) (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focusses on Smartness, a multidisciplinary topic, which is examined from four perspectives: Sensors, IoT, and Data Generation; Data and Information Processing; Actuation; and Digital Systems and Infrastructure. We see smartness in the way sensing is embedded in a system, the way data and information are processed, how a system interacts internally and with its environment, and whether a system is ubiquitous or limited by space (cloud-based or edge-enabled). This reprint contains a total of 14 chapters, which are grouped according to their areas of application: mobility and transportation, healthcare, industrial environments, and other urban infrastructures. This book covers a range of topics, including mobility; healthcare; image analysis; permeable pavements; solid-waste management; sensor node and gateway architectures; cloud, fog, and edge computing; air-quality monitoring; thermal anomalies and smart helmets in industrial environments; smart airports; smart districts; smart travel choices; sensor cities; artificially intelligent cities; platform urbanism; and more.